2010
DOI: 10.2337/db09-0131
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Interleukin-16 Protects Nonobese Diabetic Mice From Autoimmune Type 1 Diabetes by a CCL4-Dependent Mechanism

Abstract: OBJECTIVEThe progressive infiltration of pancreatic islets by lymphocytes is mandatory for development of autoimmune type 1 diabetes. This inflammatory process is mediated by several mediators that are potential therapeutic targets to arrest development of type 1 diabetes. In this study, we investigate the role of one of these mediators, interleukin-16 (IL-16), in the pathogenesis of type 1 diabetes in NOD mice.RESEARCH DESIGN AND METHODSAt different stages of progression of type 1 diabetes, we characterized I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 49 publications
2
36
0
1
Order By: Relevance
“…Its chemoattractive role for CD4þ T cells and DC is well known (28), and it has been shown to be involved in T-cell recruitment in the pancreas of NOD mice (29). These data as well as the preferential localization of CD4þ T cell and DC populations in the Ti-BALT are good arguments for a direct role of this cytokine in T-cell recruitment in these lymphoid structures.…”
Section: Discussionmentioning
confidence: 56%
“…Its chemoattractive role for CD4þ T cells and DC is well known (28), and it has been shown to be involved in T-cell recruitment in the pancreas of NOD mice (29). These data as well as the preferential localization of CD4þ T cell and DC populations in the Ti-BALT are good arguments for a direct role of this cytokine in T-cell recruitment in these lymphoid structures.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have indicated that IL16 and IL18 are pro-inflammatory cytokines involved in the pathogenesis of diabetes [13,[18][19][20]. The significant role of low-grade inflammation has been confirmed in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 73%
“…13 Furthermore, antibody-mediated neutralization of IL-16 leads to protection of NOD mice from type I diabetes. 14 Another cytokine with increased mRNA expression in T-cells from newly diagnosed compared with chronic ITP was TWEAK ( Figure 2F). The differential expression of this cytokine was also reflected at the protein level in plasma ( Figure 2G).…”
Section: Resultsmentioning
confidence: 99%